Phosphatidylcholine Liposome Accelerated Platinum Nanomachines (PLANEs) With Enhanced Penetration Capability for Thrombus Mechanotherapy - Xia, Yuqiong (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.